Pengaruh Sistem Pengendalian Internal dan Good Corporater Governance Terhadap Pencegahan Fraud Pada PT. Jasa Marga (Persero) Tbk Cabang Belmera Krakatau - Muhammad Zauki Hafiezh; Hendra Harmain; Budi Dharma (Universitas Muhammadiyah Enrekang, 2023)
This study is to find out how the Influence of Internal Control System and Good Corporate Governance on Fraud Prevention at PT. Jasa Marga (Persero) Tbk Belmera Krakatau Branch. This study uses quantitative research methods and sample collection techniques using saturated sampling techniques by disseminating questionnaire data throughout the company's population. The total sample that filled out the questionnaire data of this study was 40 people. The population in this study is PT. Jasa Marga (Persero) Tbk Belmera Krakatau Branch. Data processing data analysis uses multiple linear regression analysis with the help of SPSS software. The data tests used for multiple linear regression are quality tests and classical assumption tests. The results of this study show that the Internal Control System and Good Corporate Governance affect fraud prevention. Where control activities are carried out to assess the performance of employees with the separation of duties according to the functions and responsibilities of each employee, so that there are no concurrent positions that can be opportunities or opportunities for employees to commit fraud and the principles of GCG are always applied in the company, besides that good corporate governance can be a factor to prevent fraud, So that fraud prevention does not occur.